2018
DOI: 10.3390/antiox7080103
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Extraction of Polyphenolics from the Indigenous African Fruit Ximenia caffra and Characterization by LC-HRMS

Abstract: Indigenous and non-commercial fruits can be an important source of antioxidant polyphenols; however, the identity and content of polyphenols from non-commercial fruits are often poorly described. The study aimed to extract, identify, and quantify polyphenols from the skin of the indigenous Africa fruit Ximenia caffra, using solvent extraction. Three solvents (hexane, acetone, and 70% v/v ethanol) over three extraction times (30, 60 and 120 min) were used in a 32 full factorial experimental design to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…The polarity of the extraction solvents has been proposed as one of the critical aspects that results in different extraction efficiency [29]. TPC and TA are moderately polar compounds that can be found in most berries.…”
Section: Discussion On Each Variable That Influences the Extractionmentioning
confidence: 99%
“…The polarity of the extraction solvents has been proposed as one of the critical aspects that results in different extraction efficiency [29]. TPC and TA are moderately polar compounds that can be found in most berries.…”
Section: Discussion On Each Variable That Influences the Extractionmentioning
confidence: 99%
“…However, the fact that a similar trend was not obtained for the flavonoid contents and considering the generally low values obtained for the total flavonoid content compared to the total phenolic content might suggest the presence of more phenolic compounds in the fruit and vegetables used. Polyphenolic compounds, including phenolic and flavonoid compounds, are parts of the bioactive components in food which possess health promoting properties such as anti-inflammatory, antidiabetic and antihypertensive properties, which have been the focus of many research studies [1,[13][14][15]. Percentage (mean ± standard deviation, n = 3) of (A) total phenolic and (B) total flavonoid contents of smoothies (TPC and TFC).…”
Section: The Phytochemical Composition Of Smoothies Supplemented Withmentioning
confidence: 99%
“…However, the fact that similar trend was not obtained for the flavonoid contents and considering the generally low values obtained for the total flavonoid content compared to the total phenolic content might suggest the presence of more phenolic compounds in the fruits and vegetable used. Polyphenolic compounds including phenolic and flavonoid compounds are parts of the bioactive components in food which posse health promoting properties such as antiinflammatory, antidiabtes, antihypertensive which have been the focus of many research studies [1,[12][13][14] Studies [2,15] have reported the roles of antioxidant in preventing or ameliorating the effects of free radical which have been implicated in many diseases including diabetes, hypertension, cancer etc. Phenols and flavonoid compounds are bioactive components of foods with health promoting properties including antioxidative and anti-inflammatory properties [16].…”
Section: The Phytochemical Composition Of Smoothies Supplemented Withmentioning
confidence: 99%